A Review of Kant’s Pragmatic Anthropology: Its Origin, Meaning and Critical Significance - Somayyeh Rafigi; Muhammad Asghari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the late years of his life, Kant added the question "What is Human Being?" to his basic philosophical questions and regarded its answer the answers other questions. But what is Kant’s answer to this question? In book entitled, Kant’s Pragmatic Anthropology, Wilson attempts to explore in his uncritical works such as anthropology, religion in the bounds of only reason and education, which calls them Kant’s “philosophy of experience”, finds his answer to this question. In this work, she claims that Kant’s pragmatic anthropology is not empirical psychology, in addition to exploring in the origin and meaning of pragmatic humanism, introducing man from the perspective of this philosopher as being possess the four predisposition animal, technical, pragmatic and ethical that should try with use of his talent to attain the ultimate destiny of humanity, which is ethics and freedom. Moreover, from the point of view of this writer, reflective theological judgment is thebridge between Kant’s anthropology and his critical works that, through using them, he tried to teach his students practical knowledge in order to be able them to find their position in the social, political, and cultural world.